Human Dignity, Life and Health – Between Ambiguity and Unambiguity - Duniewska, Zofia (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Human dignity, life and health are rudimentary and the most important for man, inseparably related concepts. Determining their extensive semantic boundaries encourages special attention, reflection and consideration. These concepts have been of great interest to representatives of various sciences for centuries. The aim of the article is to bring closer how rich content is seen in these concepts and what consequences it brings. The specificity of these terms means that they are defined differently. They are not unambiguous concepts. In their ambiguity one can see advantages and disadvantages. It may enrich their conceptual scope, and unfortunately it may also lead to the loss of weight and the essence of the content contained in these concepts. Their different understandings provoke discussions and disputes, inspire to deepen and organize knowledge so important in its practical application. It is important that the content attributed to these concepts be at the service of man and human communities, contributing to respect for and effective protection of values and goods so fundamental to the individual and to the community.